2019
DOI: 10.1021/acs.joc.9b00937
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox-Catalyzed Radical Cascade Reaction To Synthesize Fluorinated Pyrrolo[1,2-d]benzodiazepine Derivatives

Abstract: A new photoredox-catalyzed cascade reaction is described to access fluorinated pyrrolo[1,2-d]benzodiazepine derivatives under mild conditions. In this process, single electron transfer (SET) between the excited state photocatalyst fac-Ir(ppy) 3 and ethyl bromodifluoroacetate initiated the regioselective radical addition to a wide range of 2-(1H-pyrrol-1-yl) anilines or indol-substituted anilines, followed by another SET process and intramolecular amidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Concerning the reaction pathway, it is not clear yet. However, based on the above experimental results and literatures, [ 24‐31 ] difluoromethylene carbene was involved as the key intermediate.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Concerning the reaction pathway, it is not clear yet. However, based on the above experimental results and literatures, [ 24‐31 ] difluoromethylene carbene was involved as the key intermediate.…”
Section: Resultsmentioning
confidence: 73%
“…How to efficiently convert it into refined products is an important scientific problem. There are already very good methods to convert it into an ester, [ 25 ] a monofluoride reagent, [ 26 ] a carbon group, [ 27 ] a α‐bromide, [ 28 ] a carbonyl group, [ 29 ] etc . (Scheme 1).…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…In this cycle, the regioselective radical addition to a broad scope of 2‐(1H‐pyrrol‐1‐yl) anilines or indole‐functionalized anilines was induced by single electron transfer (SET) between the excited state photocatalyst fac‐Ir(ppy) 3 and ethyl bromodifluoroacetate, which was further trailed by another SET cycle and intramolecular amidation (Scheme 174). [192] …”
Section: Photochemical Methods Of C−h Functionalizationmentioning
confidence: 99%
“…The Sun group found that 2-(1H-pyrrol-1-yl)anilines and 2-(1H-indol-1-yl)anilines were also good substrates to react with bromodifluoroacetate, providing various fluorinated pyrrolo[1,2-d]benzodiazepine derivatives. 196 Because of the steric disadvantage as well as entropy, the use of aryl-substituted anilines for this difluoromethylation transformation was challenging. The Li group realized the copper-catalyzed C-H [3 + 2] annulation of N-aryl-or alkyl-substituted anilines with bromodifluoroacetate (Scheme 101).…”
Section: Difluoroalkylation With Arenementioning
confidence: 99%